American Experience of Student Teaching Management of Future Teachers in Primary School - Anna Kaschuk (Pedagogical Discourse, 2013)
The question of the student teaching management of future teachers in primary school in the United States of America is studied in the article. The necessity to adapt the best global experience in Ukrainian system of higher education is grounded in an article. The author designates the purpose and the content of students’ pedagogical practice, subjects of management and the conditions of admission to probation. The main principles of student teaching are shown. The author gives a description of the characterization of an American student as an active subject of the educational process. The functional responsibilities of all participants in the control system of student teaching in higher educational institutions in the USA are summarized and described in an article.